Deep radiotherapy in the treatment of peptic ulcer - Galdós Larrú, Mario (1947)
The problem of peptic ulcer to this day was a challenge to medical science, as between chronic diseases such disease entity occupies the tenth leading cause of death and the twelfth leading cause of lost work days; latter circumstance peptic ulcer assigns great importance from the point of medical social.